(untitled) (Journal of Hama University, 2025)
The aim of the current research is to determine the role of kindergarten teachers in developing the concepts of civic education for kindergarten children. To achieve this goal, the researcher used the descriptive approach by designing a questionnaire directed at kindergarten teachers and verifying its validity and reliability, then applying it to a stratified random sample of (91) kindergarten teachers. Children in the city of Homs. The results showed the following: - The importance of developing civic concepts among kindergarten children from the point of view of kindergarten teachers came at a high degree. - The role of kindergarten teachers in developing civic concepts among kindergarten children was moderate. -Obstacles to developing civic concepts among kindergarten children from the point of view of teachers were moderate. -There are statistically significant differences between the averages of teachers’ answers to the questionnaire due to the academic qualification variable in favor of those with higher degrees on the two axes (the importance of developing civic concepts and the role of kindergarten teachers in developing civic concepts), while these differences were in favor of university degree holders on the obstacles axis. -There are statistically significant differences between the averages of teachers’ answers to the questionnaire due to the years of experience variable, in favor of those with more than 10 years’ experience on the two axes (the importance of developing civic concepts and the role of kindergarten teachers in developing civic concepts), while these differences were in favor of those with less than 5 years’ experience. On the obstacles axis. The researcher presented a set of proposals, the most prominent of which are: providing kindergarten notebooks with some enrichment activities to develop concepts of civic education among children, training kindergarten teachers during service on selecting, planning, implementing and evaluating activities that develop concepts of civic education among children, and working to provide all the necessary tools and means. The teacher implements activities that develop civic education concepts for children in kindergarten.